Suspected Primary Adrenal Lymphoma (PAL) Associated With Hemophagocytic Lymphohistiocytosis (HLH) - Kim, Tara S (J Endocr Soc, 2020)
Adrenal incidentalomas, masses noted on imaging performed for other purposes, are common, with 10% to 15% presenting as bilateral adrenal masses. These cases can be challenging as the differential diagnosis is broad, including metastatic disease, primary adrenal lymphoma (PAL), or infection, and often requiring a biopsy if initial biochemical workup is unrevealing. We present here a relevant case description, laboratory and radiologic imaging studies, and discussion of literature. A 62-year-old Korean woman presented with altered mental status and fevers. She was found to have bilateral adrenal incidentalomas and retained acupuncture needles. Adrenal workup did not show biochemical evidence of hormonal excess. Infectious workup was unrevealing, as was a metal/toxin workup due to retained acupuncture needles. Fevers and episodes of hypotension persisted which prevented the patient from obtaining an adrenal biopsy. Bone marrow biopsy was obtained for pancytopenia and revealed B-cell lymphoma with large cell morphology and few histiocytes with hemophagocytosis, raising concern for lymphoma-induced hemophagocytic lymphohistiocytosis (HLH). PAL associated with HLH was highly suspected in our patient, given the large (7 cm) bilateral adrenal masses and bone marrow biopsy findings of lymphoma. The patient was treated for diffuse large B-cell lymphoma, with clinical improvement. PAL is a rare but aggressive lymphoma with few reported cases. It should be considered in the differential for both unilateral and bilateral adrenal masses. An early diagnosis is crucial as the main treatment is chemotherapy rather than surgery and it confers a significant survival benefit.